2013
DOI: 10.1021/ef302152t
|View full text |Cite
|
Sign up to set email alerts
|

β-Cyclodextrin-Functionalized Hydrophobically Associating Acrylamide Copolymer for Enhanced Oil Recovery

Abstract: Acrylamide copolymer in the chemical flooding process plays a significant role in the field of tertiary recovery for enhanced oil recovery. Allyl-β-cyclodextrin and octadecyl dimethyl allyl ammonium chloride are utilized to react with acrylamide to synthesize a novel cyclodextrin-functionalized hydrophobically associating acrylamide polymer (HCMPAM) by redox freeradical polymerization. The microstructure of HCMPAM is the spatial network characterized by Fourier transform infrared spectroscopy and atomic force … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 44 publications
1
68
0
Order By: Relevance
“…However, the viscosity rose from 189.9 to 237.4 mPa s between 8 and 80 g/L which showed an obvious salt thickening phenomenon attributed to the hydrophobic association. 34 It was also important to note that the scope of salt thicken was wider than other literature reports 35 which showed an excellent property of salt resistance. After that the size of polymer chains were reduced by electrostatic shield and the salt thickening phenomenon disappeared after increasing the concentration of NaCl solution further.…”
Section: The Optimization Of the Synthesis Conditionsmentioning
confidence: 92%
See 1 more Smart Citation
“…However, the viscosity rose from 189.9 to 237.4 mPa s between 8 and 80 g/L which showed an obvious salt thickening phenomenon attributed to the hydrophobic association. 34 It was also important to note that the scope of salt thicken was wider than other literature reports 35 which showed an excellent property of salt resistance. After that the size of polymer chains were reduced by electrostatic shield and the salt thickening phenomenon disappeared after increasing the concentration of NaCl solution further.…”
Section: The Optimization Of the Synthesis Conditionsmentioning
confidence: 92%
“…The increased EOR was due to the thickening efficiency of the supramolecular structure formed by hydrophobic association, which could increase the molecule hydrodynamic volume. 35 The tertiary oil recovery tests C, the concentration of polymer solutions; V, the pore volume of cores; E 1 , the oil recovery ratio by water flooding; E 2 , the total oil recovery ratio by water flooding and polymer flooding; EOR 5 E 2 2E 1 . demonstrated that the synthetic DTHAP exhibited better flooding effectiveness certainly and had potential application for enhanced oil recovery.…”
Section: Enhanced Oil Recovery Experimentsmentioning
confidence: 99%
“…30,38 Shear Tolerance of the Copolymers The shear tolerance of the copolymers (2.0 g/L) was investigated, as shown in Figure 7(a). It was clear that the apparent viscosity of the copolymers decreased sharply under a shear rate of 3.7-200 s…”
Section: Articlementioning
confidence: 99%
“…This work is one of the few [19,20] that attempts to use efficient thickening supramolecular systems formed by the host-guest interaction between WSHAPs and CD polymers for EOR. The main purpose of this work is to assess the performance of the proposed supramolecular system in heavy oil recovery.…”
Section: Introductionmentioning
confidence: 99%